Anti-cancer effects of Gynostemma pentaphyllum (Thunb.) Makino (Jiaogulan). Issue 1 (December 2016) - Li, Yantao; Lin, Wanjun; Huang, Jiajun; Xie, Ying; Ma, Wenzhe
Abstract Gynostemma pentaphyllum (Thunb.) Makino (GpM) (Jiaogulan ) has been widely used in Chinese medicine for the treatment of several diseases, including hepatitis, diabetes and cardiovascular disease. Furthermore, GpM has recently been shown to exhibit potent anti-cancer activities. In this review, we have summarized recent research progress on the anti-cancer activities and mechanisms of action of GpM, as well as determining the material basis for the anti-cancer effects of GpM by searching the PubMed, Web of Science and China National Knowledge Infrastructure databases. The content of this review is based on studies reported in the literature pertaining to the chemical components or anti-cancer effects of GpM up until the beginning of August, 2016. This search of the literature revealed that more than 230 compounds have been isolated from GpM, and that most of these compounds (189) were saponins, which are also known as gypenosides. All of the remaining compounds were classified as sterols, flavonoids or polysaccharides. Various extracts and fractions of GpM, as well as numerous pure compounds isolated from this herb exhibited inhibitory activity towards the proliferation of cancer cells in vitro and in vivo. Furthermore, the results of several clinical studies have shown that GpM formula could have potential curative effects on cancer. Multiple mechanisms of action have been proposed regarding the anti-cancer activities of GpM, including cell cycle arrest, apoptosis, inhibition of invasion and metastasis, inhibition of glycolysis and immunomodulating activities.